The Relationship Between Psychological Capital and Teacher Career Commitment in Ethnic Areas of China: The Mediating Effects of Gratitude and Career Well-Being - Hu, Dong; Zhou, Tianmei; Zhou, Kaiji; Deng, Fang (Frontiers in Psychology, 2022)
The purpose of this study is to investigate the characteristics, relationships and mechanisms underlying the psychological capital, career commitment, gratitude and career well-being of teachers in ethnic regions. In total, 573 primary school and secondary school teachers in Sichuan Province (including 402 teachers in ethnic regions and 171 teachers in nonethnic regions) were investigated. Following questionnaires were used to investigate these questions: "Psychological Capital Questionnaire for Primary and Secondary School Teachers", "Gratitude Questionnaire", "Teacher Career Well-being Questionnaire" and "Career Commitment Questionnaire for Primary and Secondary School Teachers". The results show that the psychological capital of teachers in ethnic regions is higher than that of teachers in nonethnic regions. Teachers in ethnic regions have lower levels of career well-being and lower levels of gratitude than teachers in nonethnic regions. There was no significant difference in career commitment between teachers in ethnic regions and teachers in nonethnic regions. There were significant positive correlations among psychological capital, gratitude, career well-being and career commitment. Psychological capital can predict career commitment significantly and positively. The mediating effect of career well-being between teachers' psychological capital and career commitment was significant in both ethnic regions and nonethnic regions. The chain of mediating effects between gratitude and career well-being was significant in nonethnic regions. In conclusion, psychological capital can predict teacher career commitment effectively, and the prediction mechanism in ethnic regions is different from that in nonethnic regions.